Impact of Employees Motivation on Organizational Performance - Dwibedi, Lalan (Academic Voices: A Multidisciplinary Journal, 2018)
Motivation and its impact on organizational performance has always remained highly researched area and have gone through many discussions and iterations. This paper identifies the factors that effects employee motivation and examines the relationship between organizational effectiveness and employee motivation. The study focuses on the practice and observance of the two central factors, empowerment and employee recognition for enhancing employee motivation which leads to organizational performance. So organizations should design their rules, policies and organizational structures that give space to the employee to work well and appreciate them on their tasks fulfillment and achievements. Higher the motivation among employee to task accomplishment higher will be the organizational performance and success.